The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/jan.12129
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the association between obesity and asthma in children

Abstract: Aims To provide a comprehensive integration of contemporary studies focusing on the relationship between obesity and asthma in paediatric populations. Background The simultaneous increase in asthma and obesity prevalence has been widely discussed over the past twenty years. Although studies have discovered a positive correlation between the two, evidence-based findings are needed to develop nursing interventions. Data Sources An electronic database search was conducted for studies published between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 84 publications
(194 reference statements)
1
32
0
1
Order By: Relevance
“…Obesity is more common among asthmatic children, [27][28][29] and recent data suggest that obesity might also play a role in the development of AD. [30][31][32] However, these studies were primarily in school-aged children and used body mass index (BMI) as a proxy for adiposity.…”
mentioning
confidence: 98%
“…Obesity is more common among asthmatic children, [27][28][29] and recent data suggest that obesity might also play a role in the development of AD. [30][31][32] However, these studies were primarily in school-aged children and used body mass index (BMI) as a proxy for adiposity.…”
mentioning
confidence: 98%
“…Obesity has become an acute focal point of research, as it is a strong risk factor for various diseases. These include CVD, diabetes, asthma, orthopaedic diseases and some forms of cancers (3)(4)(5)(6)(7) , not to mention the social stigma and low self-esteem that obese individuals may suffer (3) .…”
Section: Overweight and Obesitymentioning
confidence: 99%
“…Most of the authors have found the existence of association between obesity and asthma in children as well [14][15][16][17][18]. However, this opinion is not shared by everyone.…”
mentioning
confidence: 99%